Evaluation Of Mycological Quality Of Spices And Potential Application Of Plant Essential Oils (Cinnamomum Cassia, Syzgium Aromaticum, And Illicium Verum) In Inhibiting Growth Of Mycotoxigenic Fungi - Nordin, Syamilah (2024)
Spices are widely used in various cuisines in Malaysia to enhance the flavour and aroma. However, the susceptibility of spices to fungal infection raises concerns about potential mycotoxin contamination if the storage conditions are favourable. Thus, this study aimed to determine the prevalence of mycotoxigenic fungi in spices marketed in Penang, Malaysia, to identify and characterize the mycotoxigenic fungi based on the morphological characteristics, molecular approaches and mycotoxin production, and to study the efficacy of selected plant essential oils (EOs) in controlling the growth of mycotoxigenic fungi. A total of 110 spice samples consisting of cumin, fennel, coriander, peppers (black pepper and white pepper), chillies (dried chilli, chilli paste and chilli powder), cinnamon, star anise, cloves, curry powder and korma powder were randomly purchased from Penang’s retail markets. The samples were analyzed for the total fungal count (ground spices), and incidence of fungal infection (whole spices). The fungal species isolated from spices were identified based on morphological and molecular approaches, and the mycotoxigenic potential was determined using the Coconut Cream Agar and HPLC method. The antifungal activity of cinnamon, clove and star anise EOs were screened using a disk diffusion assay.